2022
DOI: 10.24036/abdi.v4i2.339
|View full text |Cite
|
Sign up to set email alerts
|

Bimtek Penyusunan Rencana Pelaksanaan Pembelajaran Berbasis Kurikulum Merdeka Belajar untuk Guru di Sekolah Dasar

Abstract: Solok is one of the areas in the Province of West Sumatra, Indonesia which is in a very strategic location, located at the intersection of roads between provinces and between districts/cities in West Sumatra. However, the results of the Solok City teacher competency test in 2020 are still low. Coupled with the existence of an independent learning policy that makes teachers and policy makers nervous. This is because many teachers do not understand how to prepare RPP (learning implementation plans) based on inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Therefore, a concrete effort is needed to overcome this problem. (Nellitawati et al, 2022) revealed that training and direct technical assistance were needed regarding how to prepare teaching tools by bringing in experts who are experts in the field of Independent Curriculum teaching tools. As stated by several researchers and writers, teacher abilities and competencies can be improved through training (Mulyawan, 2012)(Sa'bani, 2017 (Rukayah, 2018) (Supentri, Jumili Arianto, Ahmal, Yuliantoro, 2020) explains that the training carried out can improve the competence and ability of teachers in developing learning tools based on independent learning.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a concrete effort is needed to overcome this problem. (Nellitawati et al, 2022) revealed that training and direct technical assistance were needed regarding how to prepare teaching tools by bringing in experts who are experts in the field of Independent Curriculum teaching tools. As stated by several researchers and writers, teacher abilities and competencies can be improved through training (Mulyawan, 2012)(Sa'bani, 2017 (Rukayah, 2018) (Supentri, Jumili Arianto, Ahmal, Yuliantoro, 2020) explains that the training carried out can improve the competence and ability of teachers in developing learning tools based on independent learning.…”
Section: Discussionmentioning
confidence: 99%